Development technology status of low permeability sandstone oil reservoirs. Issue 5 (February 2020) - Liu, Xuefen; Li, Jianfeng
Abstract: The development of oil in low permeability sand stone resources is of great significance. The paper first presented the present situation of domestic and foreign technologies in water injection, gas injection, stimulation and enhanced oil recovery of low permeability sandstone reservoirs. Then the main problem in the development of oil reservoirs with ultra-low permeability was analyzed. Finally, the paper proposed the trend of the future development of these oil reservoirs.